Field reports, Ann Johnson, fall 1990 - Johnson, Annet al (1990)
Field reports with notes on bird watching for the season and sighting submitted by Ann Johnson for fall 1990. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1990. Epson - sheet feed